216k views
1 vote
Simplify.

(3x2 + 8x)(2x − 2)
A. 6x3 + 10x2 − 16x
B. 6x3 + 16x2 − 6x − 16
C. 6x2 + 10x − 16
D. 5x2 + 10x − 16

User Hroest
by
5.1k points

2 Answers

3 votes

^algebra^

(3x2 + 8x)(2x − 2)

=3x²(2x-2)

=6x³ - 6x²

+8x(2x - 2)

=16x² - 16x

put it all together

=6x³ - 6x² + 16x² - 16x

group according to variables, then count

6x³ + (-6x² + 16x²) - 16x

=6x³ + (+10x²) - 16x

=6x³ + 10x² - 16x

FINALLY FOUND, MODERATOR!

User Pedro Almeida
by
5.9k points
5 votes

Answer:

6x3+10x2−16x or A

Explanation:

I used an algebra calculator because im too lazy to work it out.

User Pauldoo
by
4.7k points